2018
DOI: 10.3390/app8030384
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Simulation Investigation on the Characteristics of Diesel Spray Impingement Based on Droplet Impact Phenomenon

Abstract: Abstract:In order to study the characteristics of diesel spray impinging in small-size internal combustion (IC) engine, the laboratorial platform of spray impingement is used to visualize the droplet impact phenomenon. A high-speed camera is used to record the whole process of the spray. An experimental research is accomplished under the impingement phenomenon of diesel spray on the wall with a fixed injection volume of 25 mg, injection pressure of 40 MPa, wall-injector distance of 40mm and orifice diameter of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…where U is the inlet velocity of 25 m/s, dt is the time step, and dx is the minimum grid size of 1.2535 × 10 −4 m. According to equation (14), the initial time step in the transient simulation was calculated as 5 × 10 −6 seconds. Then, since the convergence criterion for the momentum, continuity, turbulence, species equations, and energy equation approached, the time-step size was gradually increased.…”
Section: Transient Simulation and Experiments Results During Steel Prementioning
confidence: 99%
See 1 more Smart Citation
“…where U is the inlet velocity of 25 m/s, dt is the time step, and dx is the minimum grid size of 1.2535 × 10 −4 m. According to equation (14), the initial time step in the transient simulation was calculated as 5 × 10 −6 seconds. Then, since the convergence criterion for the momentum, continuity, turbulence, species equations, and energy equation approached, the time-step size was gradually increased.…”
Section: Transient Simulation and Experiments Results During Steel Prementioning
confidence: 99%
“…Many researchers have investigated the heat transfer characteristics of an impinging flame with a single nozzle through an analysis and numerical simulation method with computational fluid dynamics (CFD), such as Remie et al [11], Sahu et al [12], and Tajik et al [13]. Liu et al [14] and Zhen et al [15,16] studied the effect of the hydrogen concentration on the heat transfer characteristics of a premixed liquefied petroleum gas (LPG) and hydrogen flame. The results showed that the flame temperature and NOx emission increased at high hydrogen concentrations but the CO emission decreased.…”
Section: Introductionmentioning
confidence: 99%
“…u m is the velocity at the mth position, and u a is the mean of all the velocities. The value of γ is between 0 and 1, and γ = 1 indicates a perfectly uniform distribution [21]. Figure 10 shows a comparison of the velocity uniformity index at the outlets between the basic torch and the three new torches as a function of the pressure drop.…”
Section: Comparison Of Pressure Drop and Flow Field Distribution Betwmentioning
confidence: 99%
“…The DO model covers the entire range of optical thickness and can be used to solve problems ranging from surface-to-surface radiation to radiation participating in combustion problems. The default boundary conditions were selected for the DO radiation model in ANSYS FLUENT 18.2 [21]. The absorption coefficient was modeled using the weighted sum of gray gases model (WSGGM).…”
Section: Boundary Conditions For Turbulent Combustionmentioning
confidence: 99%
“…In order to reduce the amount of materials used in spray coating and painting [6], the maximum spreading diameter is an parameter of interest. It is also particularly important in other applications, like plasma spraying [7], pharmaceutical industry [8], ink-jet printing [9], metal forming [10,11], and combustion [12,13].…”
Section: Introductionmentioning
confidence: 99%